2021
DOI: 10.35808/ersj/2124
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Choice Behaviour Toward Green Clothing

Abstract: Purpose:The article aims to identify the factors influencing consumers' choice of green clothing products in the context of the theory of consumption values. Design/methodology/approach: The research was conducted on 496 Polish consumers in December 2020 from who 212 had experience in purchasing green clothing products. Selfadministered questionnaires were distributed and structural equation modelling was used for analysis. Findings: The results show that emotional, conditional, and environmental values had si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 72 publications
(125 reference statements)
2
18
0
Order By: Relevance
“…These offcut pieces are being upcycled to create new materials for products and for store design (Kering Group, 2020a, 2020b). Indeed, the development of textile recycling is one of the ways to reduce resources consumption and pollution to the environment (Bielawska and Grębosz-Krawczyk, 2021; Jha and Veeramani, 2021; Levänen, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These offcut pieces are being upcycled to create new materials for products and for store design (Kering Group, 2020a, 2020b). Indeed, the development of textile recycling is one of the ways to reduce resources consumption and pollution to the environment (Bielawska and Grębosz-Krawczyk, 2021; Jha and Veeramani, 2021; Levänen, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A single closed-loop supply chain can be reconfigured as a multi-loop system so that while materials can be reused and recycle, products from previous life cycle can be reintroduced into the market as values (D'Adamo and Lupi, 2021;Gonc ¸alves and Silva, 2021;Leva ¨nen et al, 2021). Several studies revealed positive attitudes from the consumer's perspective towards circular fashion (Bielawska and Gre ˛bosz-Krawczyk, 2021;Gopalakrishnan and Matthews, 2018;Machado et al, 2019;Vehmas et al, 2018;Sandvik and Stubbs, 2019). According to McKinsey & Company (2020a), the prospects of developing circular fashion have never been brighter.…”
Section: Reverse Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers' green purchase intention was explained by several theories such as the theory of reasoned action (TRA) (Magnuson et al , 2017; Rausch and Kopplin, 2021; Reimers et al , 2016, 2017; Vazifehdoust et al , 2013), theory of planned behavior (TPB) (Abrar et al , 2021; Bhutto et al , 2021; Kumar et al , 2022; Tewari et al , 2022; Zheng and Chi, 2015), personal value theory (Lundblad and Davies, 2016; Steg et al , 2014; Tewari et al , 2022; Van der Werff et al , 2013, 2014) and consumption value theory (Han et al , 2017; Bielawska and Grebosz-Krawczyk, 2021; Yoo et al , 2013). Besides, researchers extended these theories mentioned above by using several well-established constructs from green literature to explain green purchase behavior such as environmental concern (Hartmann and Apaolaza-Ibáñez, 2012; Kumar et al , 2022; Park and Lin, 2020; Reimers et al , 2017; Vazifehdoust et al , 2013; Yoo et al , 2013), environmental knowledge (Abrar et al , 2021; Rausch and Kopplin, 2021; Vazifehdoust et al , 2013; Zheng and Chi, 2015), cognitive or affective involvement (Tung et al , 2017), perceived green brand benefits (Hartmann and Apaolaza-Ibáñez, 2012; Liao et al , 2020), perceived consumer effectiveness (Ellen et al , 1991; Kim and Choi, 2005; Park and Lin, 2020; Reimers et al , 2017; Yoo et al , 2013; Zheng and Chi, 2015), shopping motivations (Kumar and Yadav, 2021), different aspects of self-identity (Liu et al , 2021; White and Sintov, 2017), green self-identity (Abrar et al , 2021; Tung et al , 2017) and general environmental self-identity (Reimers et al , 2017; Schuitema et al , 2013; Van Der Werf et al , 2013, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reason for a company to embrace CSR could be environmental guilt or any other thing but it leads to other significant advantages. Waste produced by textile industries includes dyes, and chemicals, imposes environmental damages, and huge amount of waste is produced Bielawska & Grebosz-Krawczyk, 2021).…”
Section: Introductionmentioning
confidence: 99%